Towards a New Spirituality from Holistic Pedagogy - Castillo Cedeño, Rocío (2011)
This paper proposes, from a holistic perspective, a critical reflection on pedagogy as a vital activity that can contribute to building a more just and inclusive society. For that purpose, some fundamental insights in the search for new pedagogical meanings are presented, according to approaches based on exploration and imagination; playfulness and sensitivity; self-regulation, integration and inclusion; ecology and sustainable development, and complexity.